2022
DOI: 10.1093/eurjpc/zwac058
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride–glucose index in the development of heart failure and left ventricular dysfunction: analysis of the ARIC study

Abstract: Aims We aimed to investigate whether the triglyceride–glucose (TyG) index, an easy-calculated and reliable surrogate of insulin resistance, was associated with the development of heart failure (HF) and left ventricular (LV) dysfunction. Methods and results A total of 12 374 participants (mean age: 54.1 ± 5.7 years, male: 44.7%) free of history of HF and coronary heart disease at baseline from the Atherosclerosis Risk in Commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 41 publications
4
37
0
Order By: Relevance
“…Finally, the study was not designed or powered to assess the effect of cardiovascular events, but we believe that our results might represent a relevant issue in major cardiovascular event incidence. Since LDLc reductions and clinical features were similar to previous reports, 3,4,14,[21][22][23][24][25][26][27]32,34,35 this might make our results representative and useful for daily clinical practice.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Finally, the study was not designed or powered to assess the effect of cardiovascular events, but we believe that our results might represent a relevant issue in major cardiovascular event incidence. Since LDLc reductions and clinical features were similar to previous reports, 3,4,14,[21][22][23][24][25][26][27]32,34,35 this might make our results representative and useful for daily clinical practice.…”
Section: Discussionsupporting
confidence: 85%
“…11 More recently, an analysis of the Atherosclerosis Risk in Communities study involving 12,374 participants free of history of heart failure or coronary heart disease demonstrated that increase in the baseline TGGi index was associated with a 15% higher risk of heart failure. 32 Thereafter, many other lipid variables are actively involved in the atherosclerotic process that leads to clinically evident ischaemic events in our population. Thereafter, the global assessment of the lipid profile, beyond LDLc, might have a relevant role in the primary and secondary prevention of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have found independent associations between TyG index and risks of atherosclerotic cardiovascular diseases, including myocardial infarction and ischemic stroke [25,33]. In a recent analysis of data from the Atherosclerosis Risk in Communities (ARIC) study, Huang et al also reported an association between higher TyG index and higher risk of incident HF in an American population, with every standard deviation's increase in TyG index (corresponding to a TyG index of 0.6) associated with a 15% increase in risk [34]. Our study confirmed these findings in two larger cohorts from distinct geographical regions in China.…”
Section: Discussionmentioning
confidence: 99%
“…One study explored relationship between TyG index as a marker for IR and heart failure, but these authors did not observe a significant association ( 31 ). However, a recent study from the Atherosclerosis Risk in Communities study (ARIC) showed a significant association between TyG index and incident HF ( 32 ).…”
Section: Discussionmentioning
confidence: 99%